CORRELATION BETWEEN BODY MASS INDEX (BMI) AND URIC ACID LEVELS IN PRE-ELDERLY AGES IN SURABAYA - Putri Widiya Ningrum; Suhartati Suhartati; Wahyuni Dyah Parmasari (Jurnal Kedokteran Diponegoro, 2025)
Background: Uric acid is the result from the breakdown of purine compounds originating from exogenous (diet) and endogenous (results of nucleic acid catabolism). Hyperuricemia occurs when uric acid levels that exceed normal limits, which is caused by several factors, one of which is obesity.  This study aimed to determine the correlation between Body Mass Index (BMI) and uric acid levels in the elderly aged 45-59 years in patients at the Pakis Health Center, Surabaya. Objective: To analyze the relationship between Body Mass Index (BMI) and uric acid levels in pre-eldery age. Method: This research uses a cross-sectional approach with consecutive sampling. The total number of respondents in the study was 76 people. This research uses secondary data from patient medical records. Data processing uses the Spearman correlation test. Results: The study found a significant correlation between groups with  p-value of 0.004 (p < 0.05) and a correlation coefficient of 0.326. Conclusion: The research found the correlation between Body Mass Index (BMI) and uric acid levels in pre-elderly people aged 45-59 years in patients at the Pakis Health Center, Surabaya.